2019
DOI: 10.1111/jphp.12928
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gastrointestinal disease states on oral drug absorption – implications for formulation design – a PEARRL review

Abstract: Objectives Drug product performance in patients with gastrointestinal (GI) diseases can be altered compared to healthy subjects due to pathophysiological changes. In this review, relevant differences in patients with inflammatory bowel diseases, coeliac disease, irritable bowel syndrome and short bowel syndrome are discussed and possible in vitro and in silico tools to predict drug product performance in this patient population are assessed. Key findings Drug product performance was altered in patients with GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 178 publications
2
60
0
Order By: Relevance
“…Starting from a value of ∼1.5 in the stomach, it rises to ∼6.0 in the duodenum, reaches ∼7.4 in the terminal ileum, and falls again to ∼6.7 in the colon [438] . An additional consideration is that these values can vary with age, presence of food, diseases, and also by the co-administration of other drugs [439] , [440] , [441] , [442] . Finally, we note that the influence of pH on bioavailability could, in pH-disturbed states, result in underdose or overdose.…”
Section: Ph-dependent Aspects Of Pharmaceutical Therapymentioning
confidence: 99%
“…Starting from a value of ∼1.5 in the stomach, it rises to ∼6.0 in the duodenum, reaches ∼7.4 in the terminal ileum, and falls again to ∼6.7 in the colon [438] . An additional consideration is that these values can vary with age, presence of food, diseases, and also by the co-administration of other drugs [439] , [440] , [441] , [442] . Finally, we note that the influence of pH on bioavailability could, in pH-disturbed states, result in underdose or overdose.…”
Section: Ph-dependent Aspects Of Pharmaceutical Therapymentioning
confidence: 99%
“…Furthermore, knowing/exploring this interplay between those factors, patients with specific profiles (i.e., motility patterns, fluid volumes, and so on) could be treated with the appropriate drug formulation, which will perform better under those patient-centric conditions. It has been shown that gastrointestinal transit times (GTT) are increased in patients with UC [24], whereas high variability in GTT has been observed in patients with severe UC [25]. In particular, the colonic transit times in healthy volunteers have a range of 7-20 h, whereas there is a much wider range (2-97.7 h) in patients with active UC [25].…”
Section: Introductionmentioning
confidence: 99%
“…As target patient segments become progressively smaller, with each segment having unique needs from the pharmaceutical product, enabling simultaneous and independent individualization of multiple product features, i.e., multifunctional individualization, will demand a marked increase in the number of product variants. This encompasses, for example, simultaneous provision of individualized dosing [ 3 , 11 , 12 , 13 , 14 , 15 ] and individualized drug release [ 3 , 16 , 17 , 18 , 19 , 20 ], where required [ 3 ]. Individualized dosing demands an increased number of dose strengths within a pre-established dose range.…”
Section: Introductionmentioning
confidence: 99%